PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL PADA KOMITMEN, KEPUASAN KERJA DAN NIAT PINDAH KERJA DENGAN PERAN MEDIASI KEADILAN DAN KEPERCAYAAN DI RSO PROF. DR. R. SOEHARSO SURAKARTA - Paryanto, Paryanto (Jurnal Manajemen Dayasaing, 2016)
Improving the quality of hospital services can not be separated from the role of the various disciplines of health workers in hospitals, including nurses, because most hospital services are nursing services. The purpose of this study was to analyze the effect of transformational leadership style on commitment, job satisfaction and nurses’ intent to move RSO Prof. Dr. R. Soeharso Surakarta with the mediating role of justice and trust. The study also is associative causal research that seek causal influence of the variables to be studied. This research was conducted and involved nurses Orthopaedic Hospital Prof. Dr. R. Soeharso Surakarta. The number of samples of this study were 124 nurses Orthopaedic Hospital Orthopedics Prof. Dr. R. Soeharso Surakarta. The results showed that transformational leadership style influence on commitment, job satisfaction and nurses’ intent to move RSO Prof. Dr. R. Soeharso Surakarta with the mediating role of justice and trust.